Level of understanding the contract requirements of PWD 203A (Rev.2007) standard form of contract among the construction professional - Abu Bakar, Norazreen (2011)
Construction contracts are usually made in writing and using one of the standard forms available .Standard Forms of contract have been use in the Malaysian construction industry as a means to expedite contractual and legal duties for the clients who wish to avoid expensive and complex legal endeavor to arrive at an agreement with their contractor. Various forms have been drafted by various professional bodies and organization, both locally and internationally, to meet the demands of local construction market for standard form. The problems arise when the standard form is drafted by the legal people and will be implementing by the technical background people that has a little knowledge about the legal aspect. The legalese problem also takes place in the contract’s issues, which may mislead the true meaning of the particular clause and cause the people not understand at all. Not all people can understand the meaning of the contract forms. Construction contracts can be a complex subject if interpretation and administration of contract are not being handled properly. In relation to these, the objectives of the study are to determine the level of understanding the contract requirement of Standard Form of contract among the construction professional. Generally, data is collected from the structured interview to selected parties in construction area to know their extent of understanding to Standard Forms of contract. The secondary sources include books, articles, seminar papers, newspaper as well as information from electronic media database on the construction contract law. The scope of this research is to know the level of understanding of PWD 203A among the construction professional (Engineer, Quantity Surveyor and Contractor) who had an experience in this field within five to ten years. The finding from the structured interview is to shows level of understanding of PWD 203A Standard Form of contract among the construction professional. As a conclusion with this research, by using the “simple plain English”, not too long sentences and not too legal terms and phrase also can help the parties understand the contract they had entered. The study shows the medium level of understanding of PWD 203A Standard Form of contract among the construction parties.